Relationships among folate, alcohol consumption, gene variants in one-carbon metabolism and p16 (INK4a) methylation and expression in healthy breast tissues - Llanos, Adana A. (Carcinogenesis, 2015)
p16 (INK4a) is a tumor suppressor gene, frequently hypermethylated in breast cancer; this epigenetic silencing of p16 (INK4a) occurs early in carcinogenesis. The risk factors and functional consequences of p16 (INK4a) methylation are unknown. Alcohol consumption, a breast cancer risk factor, impedes folate metabolism and may thereby alter gene methylation since folate plays a pivotal role in DNA methylation. In a cross-sectional study of 138 women with no history of breast cancer who underwent reduction mammoplasty, we studied breast cancer risk factors, plasma and breast folate concentrations, variation in one-carbon metabolism genes, p16 (INK4a) promoter methylation and P16 protein expression. Logistic regression was used to estimate multivariable-adjusted odds ratios (OR) and 95% confidence intervals (CI). p16 (INK4a) methylation was negatively correlated with P16 expression (r = −0.28; P = 0.002). Alcohol consumption was associated with lower breast folate (P = 0.03), higher p16 (INK4a) promoter methylation (P = 0.007) and less P16 expression (P = 0.002). Higher breast folate concentrations were associated with lower p16 (INK4a) promoter methylation (P = 0.06). Genetic variation in MTRR (rs1801394) and MTHFD1 (rs1950902) was associated with higher p16 (INK4a) promoter methylation (OR = 2.66, 95% CI: 1.11–6.42 and OR = 2.72, 95% CI: 1.12–6.66, respectively), whereas variation in TYMS (rs502396) was associated with less P16 protein expression (OR = 0.22, 95% CI: 0.05–0.99). Given that this is the first study to indicate that alcohol consumption, breast folate and variation in one-carbon metabolism genes are associated with p16 (INK4a) promoter methylation and P16 protein expression in healthy tissues; these findings require replication.